Analisis Stabilitas Lereng Dengan Dinding Penahan Tanah Kantilever Menggunakan Program Plaxis (Studi Kasus Jalan Piyungan-Batas Gunung Kidul, Yogyakarta) - Rinanditya, Ramadhani Fajar, Ir. Renaningsih, MT, Anto Budi Listyawan, ST., MSc (2016)
The history of technological development today continues to grow rapidly. One of its effects is the technological developments of construction, a specially geotechnical engineering. To simplify the planning and calculation of performance efficiency construction, the software (program) is urgently needed. In this study, the author studied how to use the program to analyze slope stability using the Plaxis programs. The analysis is performed with the control stability of slope in Piyungan, Yogyakarta to determine the safety number. After analyzed the results show that the safety numbers were less than required, then the alternate solution reqired. The author planned alternative solution by providing a type cantilever retaining wall with concrete structures. There are two calculation methods to find the safety number, manual calculation with Fellenius method and calculation with Plaxis program. As for the soil parameters are used: soil density (γ) 15.186 kN/m3; specific gravity (GS) 2.66; cohesion (c) 15.984 kN/m2; the angle of friction (φ) 30, 44o; moisture content average 44,82%, for the condition of geological layers in the field is of clayey sand with a height of soil which detained 15.2 m. Results calculation of the stability of slopes, before using alternatives solution the safety numbers of Fellenius method obtained by the 0,95085<1.5 (not safe), while program Plaxis 0,9522<1.5 (not secure). After using the alternative solution the safety numbers of Fellenius method obtained by 1,744>1.5 (safe), while program Plaxis 1,7413>1.5 (safe). By using the retaining walls, slope safety factor be increased. Keywords: avalanche, fellenius, plaxis, retaining wall, stability of slopes